APLIKASI KONSEP KONSERVASI PADA KAWASAN BANTARAN SUNGAI STUDI KASUS: CLARKE QUAY - Purwantiasning, Ari Widyati (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
ABSTRACT As a result of excursion studies’ series in Singapore in October 2009, several studies on the region in Singapore had been summarized successfully, including the assessment of conservation areas.Singapore River as one of river bank conservation area, known as Clarke Quay, has been touched on during this excurcion studies.. This paper will examine how the concept of conservation had been applied to to this area considering to promote a Clarke Quay tourist centre area. It also will study more about how the relationship of physical elements of the city with the concept of conservation nowadays. Keywords: conservation, Clarke Quay